Synthesis of Tetrasubstituted Pyrroles from Homopropargylic Amines via a Sonogashira Coupling/Intramolecular Hydroamination/Oxidation Sequence. Issue 13 (10th September 2015) - Wang, Chan; Huang, Kaimeng; Wang, Junying; Wang, Hongkai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract A one‐pot reaction of homopropargylic amines and aryl iodides was developed in the presence of a palladium (Pd) catalyst and generated a series of tetrasubstituted pyrrole derivatives in good to high yields. This process involved a Sonogashira, intramolecular hydroamination, cyclization and oxidation sequence of reactions.